Collecting Duct Carcinoma: A Rare Entity - Ferdinant Martinus Djawa; Anny Setijo Rahaju (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACTCollecting duct carcinoma is a rare and highly aggressive subtype of renal cell carcinoma. The incidence rate is less than 1-2% of all renal tumors and usually, affect middle-aged adult, commonly in men. We reported a 76-year-old man complains of an intermittent painless gross hematuria, abdominal mass and left flank pain for approximately three months. The CT abdomen showed a slightly enhancing solid mass in the left kidney and para-aorta lymphadenopathy. Cut surfaces of the kidney showed a solid-cystic and ill-defined greyish-white tumor. Microscopically, tumor formed solid sheets and tubulopapillary structures lined by neoplastic cells, hobnailing nuclei, abnormal mitotic, and a desmoplastic stroma with lymphoplasmacytic infiltration, and the immunochemical profile were PAX8 (+) /p63 (-). Based on these findings, the diagnosis was a collecting duct carcinoma. This tumor arising from the collecting duct of Bellini in the renal medulla, accounts for less than 1-2% of all renal masses and important to be distinguished from other tumors due to differences in prognosis and therapeutic. Histopathological examination is needed to establish the diagnosis. A case of collecting duct carcinoma that occurred in a 76-year-old man has been reported. A definitive diagnosis can only be done with a detailed histopathological examination for patient management benefits.Keywords          : renal cell carcinoma, collecting duct carcinoma, urothelial carcinoma, PAX8, p63